A Phase I, open-label, dose escalation study of afatinib, in a 3-week-on/1-week-off schedule in patients with advanced solid tumors - Marshall, John (Springer US, 2012)
Background A Phase I study to determine the maximum tolerated dose (MTD) and pharmacokinetics of afatinib (BIBW 2992), a novel irreversible ErbB Family Blocker, administered orally once daily in a 3-week-on/1-week-off dosing schedule. Methods Patients with advanced solid tumors received single-agent afatinib at 10, 20, 40, 55 or 65 mg/day. Safety, antitumor activity, pharmacokinetics and pharmacodynamic modulation of biomarkers were assessed. Results: Forty-three patients were enrolled. Dose-limiting toxicities (DLTs) occurred in five patients in the dose escalation phase (1/8 at 40 mg/day; 1/6 at 55 mg/day; 3/6 at 65 mg/day). The MTD was established at 55 mg/day. In the expansion cohort at the MTD, 6 patients experienced a DLT in the first 28-day treatment period. The most frequent DLT was diarrhea. The most common adverse events were diarrhea, rash, nausea, vomiting and fatigue. Overall, the afatinib safety profile in a 3-week-on/1-week-off dose schedule was similar to that of our daily-continuous schedule. Afatinib displayed dose-dependent pharmacokinetics at doses up to and including 55 mg/day, with a terminal half-life suitable for once-daily dosing. Signs of clinical antitumor activity were observed. In biopsies taken from clinically normal forearm skin, afatinib caused a reduced proliferation rate, with a concomitant increase in differentiation of epidermal keratinocytes. Conclusion Afatinib in a 3-week-on/1-week-off schedule showed a good safety profile. The MTD was 55 mg/day, although excess DLTs in the expansion cohort indicated that the 40 mg/day dose would have an acceptable safety profile for future studies. Dose cohorts between 40 and 55 mg/day were not examined in this study.